Shifting Mandates: The Federal Reserve's First Centennial - Reinhart, Carmen M; Rogoff, Kenneth S (American Economic Review, 2013)
The Federal Reserve's mandate has evolved considerably over the organization's hundred-year history. It was changed from an initial focus in 1913 on financial stability, to fiscal financing in World War II and its aftermath, to a strong anti-inflation focus from the late 1970s, and then back to greater emphasis on financial stability since the Great Contraction. Yet, as the Fed's mandate has expanded in recent years, its range of instruments has narrowed, partly based on a misguided belief in the inherent stability of financial markets. We argue for a return to multiple instruments, including a more active role for reserve requirements.